18F-FDG PET/CT Imaging in Adrenal Cryptococcosis. (April 2017) - Jain, Tarun Kumar; Karunanithi, Sellam; Bal, Chandrasekhar; Kumar, Rakesh
Abstract : Abstract: Cryptococcosis is a fungal infection, relatively rare in the absence of impaired immunity. Lung or brain may be involved. Cryptococcal dissemination is rare in absence of impaired immunity, and documentation of alone adrenal involvement without central nervous system involvement is rare. Here, we present a case of an immunocompetent patient presented with bilateral adrenal cryptococcosis with adrenal insufficiency, without central nervous system involvement and 18 F-FDG PET/CT correctly identified the residual disease.